A Review of MUI Fatwa Number 4 of 2003 on the Standardization of Halal Fatwas Regarding the Use of Unusual Food Names in Palangka Raya - Putri, Meyrara Widya; Amin, Muhammad; Baihaki, Baihaki (Al-Mustashfa: Jurnal Penelitian Hukum Ekonomi Syariah, 2024)
The food and beverage industry in Palangka Raya City is growing rapidly, encouraging business actors to innovate by giving food names that reflect uniqueness and current trends. However, some of these food names carry negative connotations, raising controversy in a religious context. This study aims to analyze the use of unusual food names in Palangka Raya City based on MUI Fatwa Number 4 of 2003 on halal standardization. The research employs a normative legal method, using legal argumentation to address the issue. The results show that the use of food names such as Ketuyung Satan, Dr. Satan Noodles (Acute, Chronic, Inpatient, Emergency, and Critical/Coma), BurgPorn, Naughty Noodles, Crazy Rice, and Crazy Spicy Pentol does not comply with the provisions of MUI Fatwa Number 4 of 2003. The fatwa states that food and drink names must not lead to disbelief, falsehood, or prohibited elements, except for traditional names ('urf) that are guaranteed not to contain unlawful components. These findings highlight the importance of integrating innovation in food naming with adherence to religious norms.Â Keywords: MUI Fatwa; Use Food Names; Halal Food; Palangka Raya.